The Shelley-Godwin Archive: The edition of Mary Shelley’s Frankenstein Notebooks - Frederike Neuber (RIDE, 2014)
The Shelley-Godwin Archive aims to bring the widely scattered handwritten legacy of the Shelley-Godwin family together on one platform. To date, in October 2014, it is still in the beta phase. The first release in 2013 presented the edition of the Frankenstein Notebooks by Mary Shelley, the drafts of one of the most popular and reprinted works of British Romanticism. This initial publication is based on a previous print edition from 1996 by Charles E. Robinson, which has been adapted and incorporated into the Shelley-Godwin Archive's structure. In the future, this first release will be followed by an edition of the fair-copy manuscripts of Prometheus Unbound by Mary Shelley's husband Percy Shelley and in further project stages by digitized manuscripts of her parents Mary Wollstonecraft and William Godwin. Aside from the digital provision of the complete literary legacy of the Shelley-Godwin family, a long-term goal of the Shelley-Godwin Archive is to create a collaborative research environment for scholars, students and the public.